THE TEACHERS’ PERCEPTION ABOUT CRITICAL THINKING SKILLS IN ENGLISH LANGUAGE TEACHING METHODOLOGIES - Moh. Yamin; Slamet Setiawan; Syafi’ul Anam; Pratiwi Retnaningdyah (University of Kuningan, 2022)
In the current situation in which all teachers are required to participate in contextual teaching fulfilling the world dynamics and students’ need in learning, it is important to follow the dynamic of contemporary ELT methodologies. The teacher’s ability in reading, learning, interpreting, and implementing the current contemporary ELT is the must; critical thinking skills are needed so that they can be the ones taking part in this study. Critical thinking skills are not only viewed as the framework of thinking but also as the framework to increase teachers’ capacity in enlarging their views about contemporary ELT methodologies. This study aimed at presenting the new perspectives concerning contemporary ELT methodologies for non-English speaking countries through critical thinking. This research was conducted qualitatively in which the data collection was through distributing questionnaires to five lecturers aiming to ask for their perspectives about English Language Teaching Methodologies through Critical Thinking. The analysis was content analysis. The findings stated that teacher’s knowledge about contemporary ELT methodologies is needed as the basic knowledge; teachers’ motivation in learning the contemporary ELT methodologies through critical thinking skills are strengthened; and teachers’ ability in identifying and analyzing the contemporary ELT Methodologies is sharpened through critical thinking skills.